PENGARUH E-COMMERCE, MODAL USAHA, EKSPEKTASI PENDAPATAN DAN PENGETAHUAN AKUNTANSI TERHADAP MINAT BERWIRAUSAHA - Umi Maulidiyah Umi; Harfiahani Indah R.N; Luluk Qoryataini; Elsa assari; Moch Aliffudin Alfian (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2025)
Entrepreneurship holds a crucial position in a country's economy. Currently, the level of entrepreneurship in Indonesia is still low compared to other countries, making the increase in the number of entrepreneurs one of the most crucial factors in economic development. In the midst of advances in information technology, it should provide business support for generation Z in entrepreneurship, but in reality, many have not utilized it optimally. This study aims to analyze the influence of e-commerce, business capital, income expectations, and accounting knowledge on entrepreneurial interest, both simultaneously and partially. The research method used a quantitative, with a Simple Random Sampling technique. The results of this study indicate that business capital has a negative and insgnificant effect on entrepreneurial interest. Meanwhile, e-commerce, income excpectations, and accounting knowledge have a positive and significant effect on entrepreneurial interest. It can be concluded that technology, motivation, and financial factors mutually support the growth of entrepreneurial interest, rather than capital limitations.